RESEARCH ON AGRICULTURAL PRODUCERS’ BEHAVIOUR IN THE MARKET OF MINERAL FERTILIZERS IN POLAND - Piwowar, Arkadiusz (Ekonomika, 2014)
Abstract. The paper outlines the problems associated with market decisions and their extra-economic determinants in the scope of purchase of mineral fertilizers by farmers. Every purchase of fertilizers for an agricultural holding is preceded by a selection made according to an individual, complex set of criteria and factors. The complexity of the entire decision-making process undertaken by farmers increases along with the development of the market of mineral fertilizers. This intensifies the need of identifying the factors affecting the decision of an agricultural producer regarding the purchase and use of a specific fertilizer. The main goal of this publication is to present the results of studies on the behaviour of agricultural producers in the market of mineral fertilizers in Poland. The correspondence analysis was used for analysing the determinants affecting the behaviours of farmers. The results of the studies have showed that the three most important factors affecting the purchase of fertilizers by farmers are the price of a fertilizer, its quality, and the nutritional requirements of crops. The results of the analyses have also indicated that all the investigated factors were dependent on the age of agricultural producers. Besides, the other major determinants of behaviours were the education of agricultural producers and the area of their agricultural holdings.Key words: behaviours of farmers, mineral fertilizers, correspondence analysis